Improvement Of The Requirements For The Training Of Engineering Personnel In Materials Science And Technology Of Construction Materials - Xolmurodov Dilmurod Sobir o’g’li (Genius Publishing Group, 2024)
The article analyzes the role of state educational standards in the training of engineering and technical personnel in higher education, as well as the qualification requirements for the engineering and technical specialty, and the requirements for the training of specialists in "Material science and technology of construction materials" comments on improvement are presented.
Keywords: Higher education; State educational standard; qualification requirements of specialization